Psychological Empowerment and Job Satisfaction: Insights from Libyan Banking Sector - Mohamed Alhadi Khalil; Uğur Yozgat (Universitas Muhammadiyah Yogyakarta, 2021)
This study investigates the four psychological empowerment dimensions (competence, impact, meaning, and self-determination) and how they impact job satisfaction. Employee empowerment innovatively boosts the performance and capabilities of the organizations. This study is significant in the background of the Libyan banking sector working under uncertain conditions since the start of the Libyan civil war. This study proposed a theoretical framework with four hypotheses that established a relationship between competence, impact, meaning, self-determination, and job satisfaction. The study used a quantitative design to test the theoretical model using the psychological empowerment model of Spreitzer (1995) and job satisfaction with the Minnesota Satisfaction Questionnaire (MSQ). Five hundred thirty (530) questionnaires were distributed to 25 branches of banks in Libya and received 333 responses, out of which 327 were valid for the analysis. The data analysis was conducted using Structural Equation Modelling (SEM) using Partial Least Squares (PLS), aided by Smartpls 3 software. The results indicated that competence was insignificant with job satisfaction and all other three dimensions were positive and significant with job satisfaction even in the bureaucratic organizational structures. It is also interesting to note that lower and middle-level managers have the self-belief to contribute despite influencing the strategies.